Coping with Psychosocial Hazards: A Systematic Review of Young Construction Workers’ Practices and Their Determinants - Samuel Frimpong; Riza Yosia Sunindijo; Cynthia Changxin Wang; Elijah Frimpong Boadu; Ayirebi Dansoh; Rasaki Kolawole Fagbenro (Buildings, 2022)
Young construction workers employ different practices to cope with psychosocial risks, most of which prevent them from achieving mental well-being. Managing this problem has been a challenge because research on the topic is fragmented. To contribute to addressing this problem, we systematically reviewed the literature on young construction workers’ coping practices using meta-aggregation guided by the PICo and PRISMA frameworks. We sought to identify young construction workers’ coping mechanisms and the factors that influence their choice of coping practices. A total of 345 studies were retrieved, and 24 studies published between 1993 and 2022 met the inclusion criteria. Using deductive thematic analysis, we identified 28 coping practices and categorized them into eight mechanisms and three domains. Eleven determinants of young construction workers’ coping choices emerged and were classified as personal and environmental factors. This review provides knowledge for building theory on young construction workers’ coping and stresses the need for further studies on the role of influencing factors such as age, individual resilience, coping experience, religion, and spirituality. Findings from this review can serve as an evidence base for researchers, occupational health practitioners, and policy-makers for developing interventions that can promote the uptake of beneficial coping practices by young construction workers.